2021
DOI: 10.1186/s12978-020-01056-w
|View full text |Cite
|
Sign up to set email alerts
|

Modern contraceptive use among unmarried girls aged 15–19 years in South Western Nigeria: results from a cross-sectional baseline survey for the Adolescent 360 (A360) impact evaluation

Abstract: Purpose Adolescents 360 (A360) is an initiative being rolled out across Nigeria with the aim of increasing voluntary modern contraception use among women aged 15 to 19 years. Using evaluation study baseline data, we identified sexuality, fertility and contraceptive use characteristics of young unmarried girls in South Western Nigeria. Methods A cross-sectional baseline survey of unmarried girls aged 15 to 19 years was conducted in Ogun state, Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…Past studies have identified an association between rape and HIV [ 52 , 53 ]. Our prior work in Nigeria had also confirmed this association [ 33 ], plus the high incidence of rape and forced sexual initiation [ 36 ], and attendant high-risk sexual behavior adopted as a negative coping mechanism among adolescent rape survivors [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Past studies have identified an association between rape and HIV [ 52 , 53 ]. Our prior work in Nigeria had also confirmed this association [ 33 ], plus the high incidence of rape and forced sexual initiation [ 36 ], and attendant high-risk sexual behavior adopted as a negative coping mechanism among adolescent rape survivors [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Muitas vezes ao apresentar o tema aos filhos, eles podem sentir que estão corrompendo a inocência do adolescente ou incentivando a promiscuidade, entendem como um incentivo ao início da prática sexual. Frequentemente nem mesmo os pais receberam a educação adequada sobre isso (Crawford, et. al., 2021).…”
Section: Resultsunclassified
“…However, sexually active adolescents had greater level of knowledge compared to their counterparts who were less sexually active. 24 Another study yet in Nigeria, highlighted that, overall, adolescent boys were more knowledgeable on matters pertaining contraception compared to adolescent girls. Nonetheless, 61.5% of adolescent girls who participated in the study had sufficient knowledge of contraceptives.…”
Section: Adolescents' Knowledge Of Contraceptive Usementioning
confidence: 99%
“…For example, they feel ashamed to seek such services due to misinformation and the fact that society perceives these services to be for married women. 24,25 Apart from the discussed socio-demographic characteristics, other factors that affect knowledge of contraceptive use include policy, culture, religion and economic factors. According to Bekele et al adolescents who listen to radios and watch television are more exposed to such information.…”
Section: Adolescents' Knowledge Of Contraceptive Usementioning
confidence: 99%
See 1 more Smart Citation